2020
DOI: 10.1109/access.2020.3040740
|View full text |Cite
|
Sign up to set email alerts
|

GOAMLP: Network Intrusion Detection With Multilayer Perceptron and Grasshopper Optimization Algorithm

Abstract: In this paper, an intrusion detection system is introduced that uses data mining and machine learning concepts to detect network intrusion patterns. In the proposed method, an artificial neural network (ANN) is used as a learning technique in intrusion detection. The metaheuristic algorithm with the swarm-based approach is used to reduce intrusion detection errors. In the proposed method, the Grasshopper Optimization Algorithm (GOA) is used for better and more accurate learning of ANNs to reduce intrusion dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Unlike IoT devices with micro intelligence, learning systems and forecasting can be implemented in upper layers. A more robust mechanism using combinations of neural networks and metaheuristic grasshopper algorithm GOAMLP [53] can learn to predict errors in different stages and different network elements, including machinery. The machinery operators may have no access to the status.…”
Section: Management Model Requirementsmentioning
confidence: 99%
“…Unlike IoT devices with micro intelligence, learning systems and forecasting can be implemented in upper layers. A more robust mechanism using combinations of neural networks and metaheuristic grasshopper algorithm GOAMLP [53] can learn to predict errors in different stages and different network elements, including machinery. The machinery operators may have no access to the status.…”
Section: Management Model Requirementsmentioning
confidence: 99%
“…In [15], an IDS can be presented that uses ML and data mining ideas for detecting network intrusion paradigms. In the presented technique, an ANN was utilized as a learning technique.…”
Section: Related Workmentioning
confidence: 99%
“…Through multiple RL trials, the authors demonstrated that PB2 can achieve remarkable performance levels while adhering to a moderate computational budget. In another study by Moghanian et al [38], a swarm-based metaheuristic algorithm is employed to minimize errors in intrusion detection. In the novel approach, the Grasshopper Optimization Algorithm (GOA) is harnessed to enhance the precision of artificial neural networks (ANNs) in order to decrease the rate of intrusion detection errors.…”
Section: Related Workmentioning
confidence: 99%